Embodied faith in digital spaces: Reimagining Pentecostal sexual ethics through the Nicene Creed in the Fourth Industrial Revolution’s (4IR) African context - Khonani M. Maselesele; Ndidzulafhi Mudau; Mashudu E. Muthivhi (Theologia Viatorum)
Historically, Christianity wielded authority over virtue, condemning African ethics. Fourth Industrial Revolution (4IR), defined by digitals that transform intimacy, questions Pentecostal sexual ethics – generating contradictions between dogma and technoscape. This study investigates how Nicene Creed doctrines can help Pentecostals develop a paradigm for handling sexuality in 4IR-driven Africa. The study examines Pentecostalism in Africa, particularly South Africa, where tensions between indigenous sexual ethics, colonial Christianity and technological innovation present theological concerns. The study utilises a historical-theological approach, hermeneutically examining primary and secondary sources – combining a historical analysis of the Nicene Creed, examining indigenous sexuality perspectives and a theological critique of digital impact on sexual ethics. The findings show that Greco-Roman philosophy and colonial beliefs continue to influence Pentecostal sexual ethics, dismissing indigenous African perspectives. The Nicene Creed offers theological resources constructing an integrated approach, prioritising embodiment while tackling digital issues. A rebuilt Pentecostal theology of sexuality based on Nicene principles and African philosophy can offer a comprehensive approach to affirming immanence while evaluating technological developments. Subsequently, providing pastoral care, ethics and community-building resources.